83.0k views
5 votes
Find dy/dx using implicit differentiation
cos x + sin y = 1

User Ryeballar
by
4.6k points

1 Answer

3 votes

Differentiate both sides with respect to x, using the chain rule for the sine term:


\cos(x) + \sin(y) = 1


\implies -\sin(x) + \cos(y)(\mathrm dy)/(\mathrm dx) = 0

Solve for dy/dx :


-\sin(x) + \cos(y)(\mathrm dy)/(\mathrm dx) = 0 \\\\ \cos(y) (\mathrm dy)/(\mathrm dx) = \sin(x) \\\\ \boxed{(\mathrm dy)/(\mathrm dx) = (\sin(x))/(\cos(y))}

User Mbourgon
by
4.6k points